Global Attribution of Runoff Variance Across Multiple Timescales. Issue 24 (28th December 2019) - Liu, Jianyu; Zhang, Qiang; Feng, Shuyun; Gu, Xihui; Singh, Vijay P.; Sun, Peng
Abstract: Previous findings on the relative importance of driving factors to runoff have been controversial, and the relative contribution of driving factors behind the temporal variance of runoff ( Rv ) still remains unquantified at a global scale. Here, we present a new framework to quantify the driving factors behind Rv globally by decomposing Rv into the temporal variance of precipitation ( P ), potential evapotranspiration ( E 0 ), total water storage change (∆ S ), and other factors (represented by n in Budyko equation), such as climate seasonality, land cover, and human impact, at intra‐annual, interannual, and multiannual timescales. The results reveal that P controls Rv at different timescales in most parts of the globe. P has distinctly larger impacts on Rv in humid basins at the multiannual scale, while other factors have larger impacts in arid basins. We highlight the different impacts of driving factors on Rv at multiple timescales, which contradicts previous global assessments that assess the relative importance by sensitivity. Key Points: A new framework is developed to quantify the effects of precipitation, potential evaporation, storage and other factors on runoff variance Application of this framework indicates that, globally and across timescales, most variance of runoff is caused by precipitation Runoff variance is highly regulated by vegetation, particularly for intra‐annual timescale